Quality of Education: Pedagogical Aspect - F. L. Ratner; N. V. Tikhonova (Высшее образование в России)
The purpose of this paper is to analyze pedagogical approaches to the concept of the quality in higher education. The personality of a teacher is considered as a key component of quality assurance. The authors analyze the role of the teacher in modern society and teacher’s professional and personal qualities necessary to increase the effectiveness of the educational process. Particular attention is paid to comprehension of quality from the point of view of the main education process participants – students and teachers. The opinions of Russian and foreign teachers in relation to the ways to improve the quality of higher education and the effectiveness of different educational technologies are presented. Using a multidimensional approach to quality, the authors offer their conception of education quality, elements of quality and quality assurance conditions.